Ovatodiolide Targets β-Catenin Signaling in Suppressing Tumorigenesis and Overcoming Drug Resistance in Renal Cell Carcinoma. (26th May 2013) - Ho, Jar-Yi; Hsu, Ren-Jun; Wu, Chieh-Lin; Chang, Wen-Liang; Cha, Tai-Lung; Yu, Dah-Shyong; Yu, Cheng-Ping
Abstract : Dysregulated β -catenin signaling is intricately involved in renal cell carcinoma (RCC) carcinogenesis and progression. Determining potential β -catenin signaling inhibitors would be helpful in ameliorating drug resistance in advanced or metastatic RCC. Screening for β -catenin signaling inhibitors involved in silico inquiry of the PubChem Bioactivity database followed by TCF/LEF reporter assay. The biological effects of ovatodiolide were evaluated in 4 RCC cell lines in vitro and 2 RCC cell lines in a mouse xenograft model. The synergistic effects of ovatodiolide and sorafenib or sunitinib were examined in 2 TKI-resistant RCC cell lines. Ovatodiolide, a pure compound of Anisomeles indica, inhibited β -catenin signaling and reduced RCC cell viability, survival, migration/invasion, and in vitro cell or in vivo mouse tumorigenicity. Cytotoxicity was significantly reduced in a normal kidney epithelial cell line with the treatment. Ovatodiolide reduced phosphorylated β -catenin (S552) that inhibited β -catenin nuclear translocation. Moreover, ovatodiolide decreased β -catenin stability and impaired the association of β -catenin and transcription factor 4. Ovatodiolide combined with sorafenib or sunitinib overcame drug resistance in TKI-resistant RCC cells. Ovatodiolide may be a potent β -catenin signaling inhibitor, with synergistic effects with sorafenib or sunitinib, and therefore, a useful candidate for improving RCC therapy.